(3TQM ehdO GdfHi Udi Gddg Ydjg hSdes - (3GdMSf Hf Ydi Hf CMeO GdeOGHZi GdeJhaj SfI (B1170s; (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3CeG HYO gfG TQM dWja Ydi GdehdO GdTQja GdPi GNJU Hg GdTQM MSf GdeOGHZi s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ LeYg Ydi hLg GdGNJUGQ Je HMeO Gddg s
(3YdjgG Jedc HGSe eMeO GdLYaQi SfI (B1260 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B253 s
Keywords: (3GdJGQjNs